Challenges in designing and assessing student interdisciplinary learning of optics using a representation construction approach. Issue 6 (13th April 2021) - Xu, Lihua; Prain, Vaughan; Speldewinde, Christopher
ABSTRACT: There is a growing interest in the value of teachers guiding students to generate their own representations to support conceptual learning in science and across complementary subjects such as mathematics. However, this approach to an interdisciplinary focus poses challenges for programme design and learning assessment. In this paper, we report on a 10-week study with a class of Year 5 students designed to (a) facilitate learning of key concepts in the topic of optics (e.g. reflection), and (b) make meaningful links between these concepts and relevant mathematical ones (e.g. symmetry and angles). Students were expected to construct, evaluate and refine representations to explain various experienced phenomena. We report on an assessment framework developed and applied to student work. Our findings indicate (a) some subject and interdisciplinary learning gains, and (b) specific challenges around designing this kind of programme, student learning assessment and teacher understanding to support this learning.